THE The Implementation of Text-Based Teaching to Enhance Students' Reading Skills at Senior High School - Ida Bagus Gede Setia Manuaba; Kadek Lina Kurniawati; Isyarotullatifah (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to evaluate the effectiveness of the Text-Based Teaching (TBT) method in enhancing the recount text reading skills of 11th-grade students at SMK TP 45. The research employs a quantitative approach with a quasi-experimental, post-test only control group design. The population consists of all 11th-grade vocational students at the school, with two classes selected via purposive sampling: an experimental group and a control group. Data was collected using a validated 25-item multiple-choice test and structured interviews. Data analysis involves descriptive statistics, normality and homogeneity tests, and an independent sample t-test. The implementation of TBT is expected to significantly improve students' reading comprehension by focusing on text structure and linguistic features.